Chaetomitrium Horridulum - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Plants are robust, often tinged with red, and irregularly pinnate, (2) branches are generally sub-tumid; (3) branch leaves are deeply concave and strongly constricted below apices; (4) leaf margins are strongly spinose-serrate in upper half but only denticulate below; each tooth are simple, lax and almost perpendicular; (5) costae are very strong and terminated with a spine; (6) lamina cells are clearly porose, smooth but with a few scattered spines at the upper ends; (7) setae are 24 cm long and densely setulose to the base.